Detection of equid herpesviruses among different Arabian horse populations in Egypt. Issue 3 (31st May 2019) - Azab, Walid; Bedair, Sameh; Abdelgawad, Azza; Eschke, Kathrin; Farag, Gemelat K.; Abdel‐Raheim, Ali; Greenwood, Alex D.; Osterrieder, Nikolaus; Ali, Ahmed A. H.
Abstract: Equid herpesviruses (EHVs) threaten equine health and can cause significant economic losses to the equine industry worldwide. Different equid herpesviruses, EHV‐1, EHV‐2, EHV‐4 and EHV5 are regularly detected among horse populations. In Egypt, monitoring is sporadic but EHV‐1 or EHV‐4 have been reported to circulate in the horse population. However, there is a lack of reports related to infection and health status of horses, likely due to the absence of regular diagnostic procedures. In the current study, the circulation of four infectious equid herpesviruses (EHV‐1, EHV‐2, EHV‐4 and EHV‐5) among different Arabian horse populations and donkeys residing the same farm was monitored. Different samples were collected and DNA was extracted and subjected to quantitative (q)‐PCR to detect the four equid herpesviruses using specific primers and probes. Antibody titres against EHV‐1 and EHV‐4 were tested using virus neutralization test and type‐specific ELISA. The results showed that EHV‐1, EHV‐2, EHV‐4 and EHV‐5 are endemic and can be a continuous threat for horses in the absence of vaccination programs and frequent virus reactivation. There is an urgent need for introduction of active regular surveillance measures to investigate the presence of different equid herpesviruses, and other equine viral pathogens, in various horse populations around Egypt and to establish a standardized cataloguing of equine health status. Abstract : Equid herpesviruses are endemic in horse population in Egypt and can be a continuous threat for horses in the absence of vaccination programs and frequent virus reactivation. There is an urgent need for introduction of active regular surveillance measures to investigate the presence of different equid herpesviruses, and other equine viral pathogens, in various horse populations around the country and to establish a standardized cataloguing of equine health status.